2018
DOI: 10.3390/w10040493
|View full text |Cite
|
Sign up to set email alerts
|

Reference Evapotranspiration Variation Analysis and Its Approaches Evaluation of 13 Empirical Models in Sub-Humid and Humid Regions: A Case Study of the Huai River Basin, Eastern China

Abstract: Accurate and reliable estimations of reference evapotranspiration (ET 0) are imperative in irrigation scheduling and water resource planning. This study aims to analyze the spatiotemporal trends of the monthly ET 0 calculated by the Penman-Monteith FAO-56 (PMF-56) model in the Huai River Basin (HRB), eastern China. However, the use of the PMF-56 model is limited by the insufficiency of climatic input parameters in various sites, and the alternative is to employ simple empirical models. In this study, the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
3
16
0
1
Order By: Relevance
“…The spatiotemporal variations of ET are influence not only on the precipitation and land surface water availability, but also on the sensible heat flux by altering terrestrial surface temperature (Oki and Kanae, ; Zhang et al , ). In earlier studies, many researchers have frequently reported on the decreasing trends of reference evapotranspiration (ET 0 ; Xu et al , ; Dinpashoh et al , ; Huo et al , ; Chu et al , ; Nouri et al , ; Li et al , ; Li et al , ), pan evaporation (E pan ; Roderick and Farquhar, ; ; Cong et al , ; Tabari and Marofi, ; Limjirakan and Limsakul, ; Breña‐Naranjo et al , ; Li et al , ) and potential evapotranspiration (ET p ; Hobbins et al , ; Donohue et al , ; Matsoukas et al , ; Liu and McVicar, ) in different regions worldwide. Due to global warming, the increasing air temperature is anticipated to increase ET 0 , E pan and ET p , but ET 0 , E pan and ET p show decreasing trends in the aforementioned regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatiotemporal variations of ET are influence not only on the precipitation and land surface water availability, but also on the sensible heat flux by altering terrestrial surface temperature (Oki and Kanae, ; Zhang et al , ). In earlier studies, many researchers have frequently reported on the decreasing trends of reference evapotranspiration (ET 0 ; Xu et al , ; Dinpashoh et al , ; Huo et al , ; Chu et al , ; Nouri et al , ; Li et al , ; Li et al , ), pan evaporation (E pan ; Roderick and Farquhar, ; ; Cong et al , ; Tabari and Marofi, ; Limjirakan and Limsakul, ; Breña‐Naranjo et al , ; Li et al , ) and potential evapotranspiration (ET p ; Hobbins et al , ; Donohue et al , ; Matsoukas et al , ; Liu and McVicar, ) in different regions worldwide. Due to global warming, the increasing air temperature is anticipated to increase ET 0 , E pan and ET p , but ET 0 , E pan and ET p show decreasing trends in the aforementioned regions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when explaining the effects of meteorological variables on ET a and ET p change trends, only simple correlation analyses were applied in earlier studies. Nevertheless, an attribution analysis of both the ET a and ET p changes based on the CR theory in the HRB of eastern China has not been undertaken (Li et al , ; ; ). Thus, based on the problems above, the specific scientific questions are listed as follows: Is the CR theory applicable to the HRB, and is the original AA model based on CR theory suitable, and, if not, can the AA model be calibrated? Are the changing trends of ET a and ET p always linear and monotonous in the past two climatic periods? Have the dominant factors of ET a and ET p change trends shifted, and how does that influence the ET a and ET p trends considering the climate change in the nearly 60 years? …”
Section: Introductionmentioning
confidence: 99%
“…The application of ET o is also used in the studies of crop water demand. Therefore, knowledge of ET o is of great importance in agricultural water management, hydrological field, climate change, and irrigation practice 24,25 .…”
mentioning
confidence: 99%
“…The selection of an optimal empirical model for calculating the ET o is significant for agricultural water resources management, hydrological planning and irrigation designing 11,24,29 . In recent decades, a large number of empirical models have been developed to estimate the ET o , which have been widely reported in the literature (Table S1).…”
mentioning
confidence: 99%
“…Furthermore, it also has scientific and practical applications for improving not only the comprehensive management of regional water resources in a basin but also the management of water-related natural disasters at the basin scale [32]. Since the AI is obtained by the precipitation divided by potential evapotranspiration, and potential evapotranspiration is mainly influenced by four main meteorological factors (temperature, relative humidity, wind speed, and solar radiation) [6,8,33,34]. Thus, clarifying the spatial and temporal trends of AI and determining the contributions of the above five meteorological factors to the AI trends are of greater importance for understanding regional scale dryness climate change features.…”
Section: Introductionmentioning
confidence: 99%